Adopting Lesson Study on Job Training in Toyama School Japan to Biology Education School Field Introduction Program - Herlanti, Yanti (Universitas Pendidikan Ganesha, 2024)
Lesson study is applied as a method to improve the teaching skills of prospective teachers when teaching practice in schools. Indonesia uses the term School Field Introduction (PLP) for practical teaching activities in schools, while in Japan, the term On Job Training (OTJ) is used. This study aims to analyze the differences in lesson study methods practiced in universities in Indonesia and Japan, then adapts the lesson study method OTJ to apply in the PLP II course. The research method was carried out by direct and indirect observation. Indirect observation is through the YouTube channel of lesson study practices on PLP II at one of the universities. Direct observation and in-depth interviews were conducted with OTJ at Japan's Affiliated Toyama University Junior High School. The adaptation of the Japanese OTJ was carried out in three stages. The first was conducted in two schools in Jakarta and Depok, involving two teachers and eight students. The second and third were conducted in one school in Depok, involving one teacher and four students. The study results show differences between lessons developed in Indonesia and Japan. OTJ in Japan emphasizes collaboration and cooperation among prospective teacher in improving teaching skills. Meanwhile, in PLP in Indonesia, the emphasis is on collegiality among prospective teachers, tutor teachers, and supervisor lecturers. Applying the Japanese OTJ to PLP II in Biology Education showed that this method can increase prospective teacher-students’ confidence, improve creativity in teaching methods and media.